Saturday

April 19, 2014

April 19, 2014

Posted by **Janice** on Monday, February 4, 2013 at 7:38am.

2a-3b=6

- Math -
**Reiny**, Monday, February 4, 2013 at 8:53amI assume we are solving ?

first times 3 ---> 9a + 12b = -75

2nd times 4 ---> 8a - 12b = 24

add them

17a = -51

a = -3

back into the first:

3(-3) + 4b = -25

4b = -16

b = -4

a = -3 , b=-4

**Related Questions**

alegbra - (2a+4b)-(3a-b)when and how do u know to change the signs? It might ...

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

Pre-Calc-please check - Please check this for me expand (3z-2b)^5 using Binomial...

?? - 2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = ...

Algebra 2345678!! - Solve the system of equations using the Addition method. 2a...

math - simplify this 2a+3b-c+(a-b-c)-(2a-4b+3c)

Math - In this problem: -2/a+2 + 3a/2a-1 First I made the denominators alike: -2...

algebra 1 - a+(3a-2a)-(4a-3b) Combine the "a" tems and you can reduce this to _?...

Algebra 1 - Can someone plz solve this 2a+3b-c+(a-b-c)-(2a-4b+3c)

Algebra - Can you solve this problem? 2a+b/(a-b)(a-2b) - a+4b/(a-b)(a-3b) - a-7b...